Studi Flexing dalam Pandangan Hadis dengan Metode Tematik dan Analisis Etika Media Sosial - Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
The flexing action was rife on social media and was widely criticized. This study aims to discuss the case of flexing according to the view of the hadith. This study uses a qualitative approach by applying thematic methods. The formal object of this research is Islamic morals and social media ethics which are formulated based on hadith themes. The object of this research is flexing behavior in the context of the post truth era. The results of this study indicate that hadith themes can be formulated within the theoretical framework of Islamic morals and social media ethics. The discussion of this study explains that flexing is not relevant to the moral aspects of Islam which include honesty, humanity, and peace and is not in line with the ethical aspects of social media which include education, profession, and impact. The conclusion of this study is that flexing behavior is full of negative impacts so that it is contrary to Islamic morals and social media ethics which are formulated according to the thematic framework of hadith along with the post truth era.